Interpretation of the Geological Romance of Kendari Bay Using Landsat 5 TM - Makkawaru, Andi; Sideng, Uca; Sufrianto, Sufrianto (LaGeografia, 2021)
Kendari Bay is part of Kendari City. Kendari Bay is a city landmark in addition to its economic and environmental functions.. The condition of Kendari Bay is experiencing a fairly high sedimentation problem, so that it begins to cause problems with land availability and space utilization patterns in the Kendari Bay area. The endogenous process of dynamic earth activities is a part that needs to be considered in managing that problems. This study aims the geological conditions of Kendari Bay by using remote sensing as a form of studying the geological conditions of Kendari Bay. Using Landsat 5 TM imagery in 1990, it was used to see the natural geological conditions of Kendari Bay, using the false color composite method and interpretation of photo images visually and validated through field observations. Landsat image processing and interpretation using Quantum GIS, resulted in Kendari bay can be divided into several physiography, namely coastal zone, estuary zone, fluvial zone, plain zone, hill zone, and mountain zone (Head land). The physiography can be seen from the geological characteristics such as the lithology which is composed of alluvial deposits to limestone. The results of interpretation of composite color images and validation of direct observation data in the field show a qualitative suitability.